2018
DOI: 10.1186/s13058-018-1045-4
|View full text |Cite|
|
Sign up to set email alerts
|

Consistent and reproducible cultures of large-scale 3D mammary epithelial structures using an accessible bioprinting platform

Abstract: BackgroundStandard three-dimensional (3D) in vitro culture techniques, such as those used for mammary epithelial cells, rely on random distribution of cells within hydrogels. Although these systems offer advantages over traditional 2D models, limitations persist owing to the lack of control over cellular placement within the hydrogel. This results in experimental inconsistencies and random organoid morphology. Robust, high-throughput experimentation requires greater standardization of 3D epithelial culture tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…Movies 1 and 2). This is consistent with the activity of non-tumorigenic MCF-12A cells in previous findings which move between print locations and continue to display movement within organoids 23 . Importantly, as these structures began to generate branched extensions, tumor cells remained equally dispersed within the networked structures (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Movies 1 and 2). This is consistent with the activity of non-tumorigenic MCF-12A cells in previous findings which move between print locations and continue to display movement within organoids 23 . Importantly, as these structures began to generate branched extensions, tumor cells remained equally dispersed within the networked structures (Fig.…”
Section: Resultssupporting
confidence: 92%
“…To improve efficiency of chimeric structure formation, we next sought to guide the formation of chimeric organoids using our custom bioprinting system. We previously described our ability to standardize the frequency of organoid formation through control of the initial cell quantities within bioprinted cell-deposits; cell-deposits containing at least 40 cells formed organoids within 7 days post-printing 23 . Therefore, we mixed MCF12A cells and tumorigenic MCF-7 or MDA-MB-468 cells in a 5:1 ratio as above, and then printed 66 nl of cell mixtures equivalent to 40 cells in equally-spaced linear (300 µm) and circular (500 µm) arrays inside collagen I gels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organoids have been used in a staggering number of applications, including intestinal, cerebral, pancreatic, kidney, hepatic, retinal, lung, colonic, gastric, thyroid, prostate, salivary, mammary, lingual, placental, and spinal tissues, which are reviewed elsewhere [ 88 ]. Bioprinting has only recently seen application in organoid literature [ [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] ]. In coaxial systems, developing organoid tissues might be printed within a sacrificial sheath hydrogel, allowing for mechanical strength and hierarchal arrangement, without compromising cell viability ( Fig.…”
Section: Applications Of Coaxial Printingmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported a typesetting error in the spelling of the second author’s name.…”
Section: Correctionmentioning
confidence: 99%